Development and evaluation of a novel modified release pellet-based system for the delivery of desloratadine and pseudoephedrine hydrochloride - Kushare, Sachin U; Phatak, Atul A; Chaudhari, Praveen D (Asian Journal of Pharmaceutics (AJP), 2014)
Modified-release multiple unit dosage form (MRMUD) of desloratadine and pseudoephedrine hydrochloride with different release profiles were prepared. The MRMUD system consists of the immediate-release pellets containing desloratadine and sustained release pellets containing pseudoephedrine hydrochloride.The immediate and sustained release pellets were prepared by solution layering technique. A 32 full-factorial design was employed to optimize the sustained release formulation where in polymer ratio (Ethyl cellulose : hydroxyl propyl methyl cellulose) (X1) and % polymer coating (X2) were taken as independent variables and amount of drug release, in 0.1N HCl (Y1), after 10 haves (Y2) were taken as the dependent variables. Optimization studies were carried out using the Design Expert Software. Formulations were evaluated for in vitro release studies, the release data were evaluated by the model dependent (curve fitting) method using the PCP Disso software. The in vitro drug release followed Hixson-Crowell model and the drug release mechanism was found to be anomalous or non-fickian type. It was found that proper combination of ethyl cellulose and hydroxy propyl methyl cellulose polymer, % polymer coating and process parameters could provide sustained release of pseudoephedrine hydrochloride for a period of 12 haves.